2018
DOI: 10.2340/00015555-2938
|View full text |Cite
|
Sign up to set email alerts
|

Structured Diagnostic Approach and Risk Assessment in Mucous Membrane Pemphigoid with Oesophageal Involvement

Abstract: Oesophageal involvement in mucous membrane pemphigoid is considered rare, but it may be underdiagnosed. To assess the incidence of oesophageal involvement in a group of patients with newly diagnosed mucous membrane pemphigoid we retrospectively analysed the medical records of 30 consecutive patients with mucous membrane pemphigoid diagnosed between 2006 and 2016 at the Department of Dermatology, University Hospital Würzburg. Twenty-one patients (70%) reported symptoms indicative of oesophageal mucous membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…For the diagnosis of MMP, multiple examinations, including histological and immunological confirmation are required in most cases 1 . Tissue separation at the basement membrane zone (BMZ), which suggests subepithelial blisters in H&E staining is one of the most critical findings in the histological examination for MMP 11 . Immunological examinations are required to specify autoantibodies, particularly, tissue‐bound autoantibodies can be detected by direct immunofluorescence (DIF).…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnosis of MMP, multiple examinations, including histological and immunological confirmation are required in most cases 1 . Tissue separation at the basement membrane zone (BMZ), which suggests subepithelial blisters in H&E staining is one of the most critical findings in the histological examination for MMP 11 . Immunological examinations are required to specify autoantibodies, particularly, tissue‐bound autoantibodies can be detected by direct immunofluorescence (DIF).…”
Section: Discussionmentioning
confidence: 99%
“…In the acute attack of pemphigus vulgaris, oesophageal involvement was confirmed in 12/26 (46.2%) Turkish patients investigated 59 . In a German study of 30 patients with MMP, 9 out of 12 under examination was found to have oesophageal lesions 60 . A Brazil study of 12 patients with EBA demonstrated oesophageal involvement in 4 of 10 patients undergoing endoscopy 61 .…”
Section: Gi Involvement In Autoimmune Bullous Dermatosesmentioning
confidence: 95%
“…59 In a German study of 30 patients with MMP, 9 out of 12 under examination was found to have oesophageal lesions. 60 A Brazil study of 12 patients with EBA demonstrated oesophageal involvement in 4 of 10 patients undergoing endoscopy. 61 Pemphigus vulgaris and bullous pemphigoid are rare causes of oesophagitis dissecans superficialis (sloughing oesophagitis), which may lead to acute GI bleeding.…”
Section: Gi Involvement In Autoimmune Bullous Dermatosesmentioning
confidence: 99%
“…In addition, such examination does not always reveal subepithelial blisters, because of tissue destruction (27). Immunologically, the deposition of IgG autoantibodies and C3, or sometimes of IgA autoantibodies, at the BMZ can be detected by direct immunofluorescence (DIF) of lesional or perilesional samples (1, 28). To identify circulating autoantibodies to the BMZ, indirect immunofluorescence (IIF) with normal human skin as the substrate is usually performed, but autoantibodies are detected in only 17–53% of MMP cases (5, 17, 18, 29).…”
Section: Issues In Diagnosing Mmpmentioning
confidence: 99%